2006
DOI: 10.1002/tea.20098
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of Zimbabwe high school chemistry students' laboratory work–based images of the nature of science

Abstract: This study investigates the proximal and distal images of the nature of science (NOS) that A‐level students develop from their participation in chemistry laboratory work. We also explored the nature of the interactions among the students' proximal and distal images of the NOS and students' participation in laboratory work. Students' views of the NOS and the nature of their chemistry laboratory work were elicited through students' responses to an open‐ended questionnaire and semistructured interviews. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 36 publications
3
15
0
1
Order By: Relevance
“…Finally, for the ''modelers,'' in case of a conflict between theory and experimental evidence, they realized that both theory and experimental procedure and data need scrutiny. This is in line with the findings of Vhurumuku et al (2006). In contrast, the outcome of the study by Ryder and Leach (2000) revealed that most of the European students in their sample suggested more weight should be given to experimental data (evidence) for the construction of scientific knowledge.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Finally, for the ''modelers,'' in case of a conflict between theory and experimental evidence, they realized that both theory and experimental procedure and data need scrutiny. This is in line with the findings of Vhurumuku et al (2006). In contrast, the outcome of the study by Ryder and Leach (2000) revealed that most of the European students in their sample suggested more weight should be given to experimental data (evidence) for the construction of scientific knowledge.…”
Section: Discussionsupporting
confidence: 80%
“…For instance, teaching the model of the atom requires a familiarization with the idea of the indivisible particles of Dalton and Thompson's discovery of the electron, to the nuclear atom of Rutherford and Bohr's orbital model. For the foundation students in the sample, comprising mainly black students, the similarity of the findings to those from a study of Zimbabwean students (Vhurumuku et al, 2006) may suggest a cultural influence on several aspects of views of the NOS (see also Sutherland & Dennick, 2002). An emphasis, across African cultures, on inclusiveness and consensus rather than competition (Nsamenang, 1999;Ramos, 2002;Venter, 2004), and a predominant culturally determined interaction pattern of cooperation (Jegede, 1997), may encourage the view of equal status of experimental data and theory in the construction of scientific knowledge, and thus highlight the need to reconsider both in case of a conflict.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Обзор научной литературы. Курс физики и другие общеобразовательные дисциплины в высшей школе ориентированы на решение задач развития у студентов навыков, необходимых для формирования самостоятельных высококвали-фицированных специалистов [Reid, 2007;Feisel, 2005;Vhurumuku, 2006]. Необходимыми каче-ствами профессионала являются способность и потребность последовательно и логически мыс-лить, планировать и организовывать работу, об-ращаться с приборами и гаджетами, уметь пере-нести эти навыки в будущую жизнь и работу.…”
Section: Abstract: Vocational Training Competency-based Approach Inunclassified